(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
A horrific example of cultural customs and society standards that put family honour ahead of personal freedom and rights are honour murders. throughout spite of societal disapproval and legal restrictions, these heinous crimes—which are mostly committed against women—recur throughout India. Examining the issue of honour murders in India, this study focuses especially on the important role that traditional caste-based councils known as Khap Panchayats play in rural areas. Honour murders are first contextualised in the study within the larger framework of patriarchal systems and deeply ingrained gender norms that characterise Indian culture. It also emphasises how political and law enforcement officials in the area have allowed honour killing offenders to operate with impunity, therefore highlighting the systemic character of the issue. The report also looks at community-based awareness programmes, grassroots activity, and legislative actions meant to stop honour murders and question Khap Panchayat power. It underlines the need of confronting underlying sociocultural beliefs and enabling underprivileged people—women in particular—to stand up for their rights and oppose repressive policies. This study emphasises how urgently multidimensional approaches—including legislative changes, societal mobilisation, and educational programmes meant to question regressive norms and undermine caste-based oppressive systems—are needed to end honour murders in India. It urges coordinated measures to hold offenders and their supporters responsible and to promote gender equality and human dignity.